Production And Operations Management. - Mühlemann, Alan.; Oakland, John S.; Lockyer, K. G. (Pitman, 1992)
Structured around the 5 Ps model - Product, Plant, Processes, Programmes and People - this text considers production and operations management. This edition contains greater coverage of quality and reliability, short-term forecasting and new material on OPT, MRP and MRP(II).